A New Four-Parameter Inverse Weibull Model: Statistical Properties and Applications. (13th June 2022) - Yahia, Nagla; Alsadat, Najwan
Abstract : A four-parameter Type II Topp Leone generalized inverse Weibull (TIITLGINW) model is suggested. The reliability study of the new model is provided. Quantiles, moments, moment generating function, and probability weighted moment are some of the mathematical properties being researched. The maximum likelihood (ML) estimate is employed for TIITLGINW parameters. A simulation study is conducted to estimate the model parameters of the TIITLGINW model. A single real-world collection of data is used to analyze TIITLGINW's significance and accessibility.